2013
DOI: 10.1007/s00402-013-1815-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of GSB III elbow prostheses and risk factors for revisions

Abstract: The results indicate a good long-term prognosis for this design. The prognosis has to be adjusted for the underlying disease. Previous operations such as joint reconstruction significantly increase the risk of revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In contrast, two other cohort studies reported higher reoperation rate, revision rate, and inferior implant survival in the post-traumatic group. 9,10 Rather than an overall risk comparison, we compared each implant failure mode and noted a higher risk of septic loosening in the RA group and a higher risk of bushing wear, axle failure, component disassembly, and component fracture in the post-traumatic group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, two other cohort studies reported higher reoperation rate, revision rate, and inferior implant survival in the post-traumatic group. 9,10 Rather than an overall risk comparison, we compared each implant failure mode and noted a higher risk of septic loosening in the RA group and a higher risk of bushing wear, axle failure, component disassembly, and component fracture in the post-traumatic group.…”
Section: Discussionmentioning
confidence: 99%
“…Among all, disassembly accounted the majority of the failure modes in the post-traumatic group. 10 Morrey et al 29 reported a consecutive series of 55 TEAs in patients with post-traumatic arthritis. Patients had mostly undergone two operations before the TEA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current data show a revision-free survivorship of 96.1 % and 92.9 % at 5 and 10 years, respectively, for total shoulder replacement in rheumatoid patients. Within our institution, the survival rates of rheumatoid patients following implantation of a GSB III elbow prosthesis are 85 % at 10 years and 69 % at 20 years [ 10 ]. The risk of revision in rheumatoid patients is generally lower compared to post-traumatic conditions.…”
Section: Long-term Outcomementioning
confidence: 98%